Long-term treatment with oral N-acetylcysteine: Affects lung function but not sputum inflammation in cystic fibrosis subjects. A phase II randomized placebo-controlled trial - Conrad, C.; Lymp, J.; Thompson, V.; Dunn, C.; Davies, Z.; Chatfield, B.; Nichols, D.; Clancy, J.; Vender, R.; Egan, M.E.; Quittell, L.; Michelson, P.; et al. (Journal of cystic fibrosis, 2015)
To evaluate the effects of oral N-acetylcysteine (NAC), which replenishes systemic glutathione, on decreasing inflammation and improving lung function in CF airways. A multicenter, randomized, double-blind proof of concept study in which 70 CF subjects received NAC or placebo orally thrice daily for 24weeks. Endpoints: primary, change in sputum human neutrophil elastase (HNE) activity; secondary, FEV1 and other clinical lung function measures; and safety, the safety and tolerability of NAC and the potential of NAC to promote pulmonary hypertension in subjects with CF. Lung function (FEV1 and FEF25–75%) remained stable or increased slightly in the NAC group but decreased in the placebo group (p=0.02 and 0.02). Log10 HNE activity remained equal between cohorts (difference 0.21, 95% CI −0.07 to 0.48, p=0.14). NAC recipients maintained their lung function while placebo recipients declined (24week FEV1 treatment effect=150mL, p<0.02). However no effect on HNE activity and other selected biomarkers of neutrophilic inflammation were detected. Further studies on mechanism and clinical outcomes are warranted.